2004
DOI: 10.1038/sj.bjc.6601604
|View full text |Cite
|
Sign up to set email alerts
|

MUC4 mucin expression in human pancreatic tumours is affected by organ environment: the possible role of TGFβ2

Abstract: MUC4 is highly expressed in human pancreatic tumours and pancreatic tumour cell lines, but is minimally or not expressed in normal pancreas or chronic pancreatitis. Here, we investigated the aberrant regulation of MUC4 expression in vivo using clonal human pancreatic tumour cells (CD18/HPAF) grown either orthotopically in the pancreas (OT) or ectopically in subcutaneous tissue (SC) in the nude mice. Histological examination of the OT and SC tumours showed moderately differentiated and anaplastic morphology, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
0
17
1
1
Order By: Relevance
“…This result does not agree with a previous similar study [23] in pancreatic cancer cell lines, implying that not only methylation but also other mechanisms, including histone modification [22], various transcription factors, growth factors, cytokines and other components [36][37][38][39][40] may regulate the expression of MUC4 in vivo.…”
Section: Discussioncontrasting
confidence: 74%
“…This result does not agree with a previous similar study [23] in pancreatic cancer cell lines, implying that not only methylation but also other mechanisms, including histone modification [22], various transcription factors, growth factors, cytokines and other components [36][37][38][39][40] may regulate the expression of MUC4 in vivo.…”
Section: Discussioncontrasting
confidence: 74%
“…Alterations in glycosylation influence growth, differentiation, transformation, adhesion, metastasis, and immune surveillance of the tumor (4). In breast cancer, the presence of increasing concentrations of highly glycosylated proteins (mucins) and other changes in glycosylation correlate with increasing tumor burden and poor prognosis (3).…”
mentioning
confidence: 99%
“…17 The microenvironment has also been shown to modify the phenotype of pancreatic cancer cells in xenografts. 18 For CDX2 in the context of CRCs, histopathological analyses have reported that gene expression is low in invasive cells but restored in metastases at the level corresponding to the primary tumors. 3 However, there was still no experimental evidence for the dynamic nature and reversibility of these CDX2 changes.…”
mentioning
confidence: 99%